(untitled) (Baghdad Science Journal, 2025)
Background: In advanced diabetes mellitus, serum levels of the most hormones are altered due to several interplaying mechanisms. Objective: To assess the relation of serum leptin and lipid profile in type 2 diabetic nephropathy. Patients and Method: Serum leptin levels and its relation to lipid profile were estimated in 62 patients with type 2 diabetic nephropathy attending the National Diabetes Center in Al- Mustansiriya University, and (26) healthy individuals considered as control group. The diabetic patients were classified into three groups, (24) pathients with normoalbuminuria (21) patients with microalbuminuria and (17) patients with macroalbuminuria. Fasting plasma glucose, serum creatinine, Hb A1c %, lipid profile (Total cholesterol, LDL- Cholesterol, HDL- Cholesterol and Triglyceride) and urinary albumin, were measured to establish the possibility of using these biomarkers as a supplementary to serum leptin to be a diagnostic test for type 2 diabetic nephropathy. Results: Serum leptin levels showed a significant elevation in microalbuminuria (20.08± 4.50 ng/ml) and macroalbuminuria groups (22.35± 6.89 ng/ml) as compared to nondiabetic normal control group (10.64 ± 3.17 ng/ml). There was no significant differences observed in serum leptin levels between the normoalbuminuria group (13.96 ± 5.73 ng/ml) and healthy controls, but a significant positive differences were noticed in the levels of fasting plasma glucose, serum creatinine, Hb A1c% and lipid profile in the three patient groups in comparison with the control group. While no significant correlation was observed between these biomarkers levels and serum leptin values. Conclusion: It might be concluded that serum leptin levels were elevated in type 2 diabetic patients with microalbuminuria and macroalbuminuria, suggesting that renal leptin degradation is impaired in early stage of kidney damage and this impairment increase with the progression of this disease. Leptin hormone may consider according to these results as a risk factor for progression of kidney disease in diabetic patients.